Colon-rectum/Colon-retto (C18.9-20.9) - C-reactive protein levels and 5-Fu induced oral mucositis in colorectal cancer patients chemotherapy with 5-fluorouracil based regimens / Valutazione dei livelli di proteina C-reattiva e mucositi orali indotte da 5-Fluorouracile (5-Fu) in pazienti con cancro colon rettale sottoposti a chemioterapia con regimi di 5-Fu - Zeng, Y.-C.; Xiao, Y.-P.; Chi, et al., F. (European Journal of Oncology and Environmental Health, 2012)
Aims: The aim of this study was to evaluate the relationship between C–reactive protein (CRP) levels and the grade of 5–Fu induced oral mucositis in colorectal cancer patients chemotherapy with 5-fluorouracil based regimens. Materials and Methods: This study was performed in 47 patients treated with 5-fluorouracil based regimens. Serum CRP levels were initially tested on the day before chemotherapy. Subsequently the serum CRP levels were measured on the second day during chemotherapy, on the first day after chemotherapy, on the second day after chemotherapy and on the third day after chemotherapy. Oral mucositis were evaluated by oncologists on days of blood sampling. Results: The distribution of the most severe mucositis was Grade I mucositis in 17.0% (8) of the patients, Grade II in 14.9% (7) of the patients and Grade III in 10.6% (5) of the patients. Statistical analysis indicated a significant rise in the CRP levels (p